Indonesian Perspectives on Inclusion: Teachers, Parents, and Students Perspective - Heryati, Euis; Ratnengsih, Een; Faatinisa, Esty (Journal of ICSAR, 2019)
One of the most significant changes in education over the past few decades has been the movement towards inclusive education. Many schools are encouraged to implement an inclusive approach in accepting and educating students with disabilities. One of the disabilities students encounter in the regular class is learning disability (LD). This study uses a case study approach to examine the perspectives of students with LD, parents of students, and classroom teachers in regular schools that held inclusive education. A number of similarities and differences in perspective between students, parents, and teachers in each case were identified. Similarities and differences in perspective were also found between each case. Some practical implications will emerge from this study.